2020
DOI: 10.1021/acs.inorgchem.0c01534
|View full text |Cite
|
Sign up to set email alerts
|

Stark Sublevel-Based Thermometry with Tb(III) and Dy(III) Complexes Cosensitized via the 2-Amidinopyridine Ligand

Abstract: Amidine-based ligand frameworks were employed to isolate a series of mononuclear lanthanide complexes. The employed N-2-pyridyl­imidoyl-2-pyridyl­amidine (Py2ImAm) undergoes metal-assisted hydrolysis yielding the ligand 2-amidino­pyridine (PyAm), which coordinates to the lanthanide ions affording [Ln­(acac)3(PyAm)], where Ln = Eu­(III) (1), Gd­(III) (2), Tb­(III) (3), Dy­(III) (4) along with the Y­(III) analogue (5). The Eu­(III), Tb­(III), and Dy­(III) congeners exhibit characteristic emissions of red, green,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…However,t he diluted species 1d displayed the emission spectra for Dy III when excited at 280 nm. We confirm thus the antenna effect from the benzoato ligands.T he quantum yield of the emission was relatively high for aD ycomplex (QY = 4%), [41,42] and the luminescent lifetime was 50 ms(Figure 5). It is concluded that high concentration of Dy III centers in 1 quenches the luminescence.Once the Dy III ions are isolated in 1d,luminescence can be observed.…”
Section: Methodsmentioning
confidence: 99%
“…However,t he diluted species 1d displayed the emission spectra for Dy III when excited at 280 nm. We confirm thus the antenna effect from the benzoato ligands.T he quantum yield of the emission was relatively high for aD ycomplex (QY = 4%), [41,42] and the luminescent lifetime was 50 ms(Figure 5). It is concluded that high concentration of Dy III centers in 1 quenches the luminescence.Once the Dy III ions are isolated in 1d,luminescence can be observed.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Other authors also report a variety of methodologies to evaluate optical thermometry. [34][35][36][37] With the purpose of demonstrating the thermometric potential of the studied complexes, the effect of temperature on the total area of the emission bands was analysed. Basic thermometer performance parameters were calculated for TbL 1 NO 3 and TbL 3 NO 3 , which showed the greatest intensities.…”
Section: Resultsmentioning
confidence: 99%
“…We confirm thus the antenna effect from the benzoato ligands. The quantum yield of the emission was relatively high for a Dy complex (QY = 4 %), [41, 42] and the luminescent lifetime was 50 μs (Figure 5). It is concluded that high concentration of Dy III centers in 1 quenches the luminescence.…”
Section: Resultsmentioning
confidence: 99%